Highly permeable artificial water channels that can self-assemble into two-dimensional arrays - Shen, Yue-xiao (Proc Natl Acad Sci U S A, 2015)
Bioinspired artificial water channels aim to combine the high permeability and selectivity of biological aquaporin (AQP) water channels with chemical stability. Here, we carefully characterized a class of artificial water channels, peptide-appended pillar[5]arenes (PAPs). The average single-channel osmotic water permeability for PAPs is 1.0(±0.3) × 10(−14) cm(3)/s or 3.5(±1.0) × 10(8) water molecules per s, which is in the range of AQPs (3.4∼40.3 × 10(8) water molecules per s) and their current synthetic analogs, carbon nanotubes (CNTs, 9.0 × 10(8) water molecules per s). This permeability is an order of magnitude higher than first-generation artificial water channels (20 to ∼10(7) water molecules per s). Furthermore, within lipid bilayers, PAP channels can self-assemble into 2D arrays. Relevant to permeable membrane design, the pore density of PAP channel arrays (∼2.6 × 10(5) pores per μm(2)) is two orders of magnitude higher than that of CNT membranes (0.1∼2.5 × 10(3) pores per μm(2)). PAP channels thus combine the advantages of biological channels and CNTs and improve upon them through their relatively simple synthesis, chemical stability, and propensity to form arrays.